2009
DOI: 10.1080/00015458.2009.11680494
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of 74 Laparoscopic Repairs of Abdominal Incisional Hernias

Abstract: Although the morbidity/mortality rates are acceptable, technical improvements must be found to reduce the recurrence rate, in particular for large incisional hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In smaller series of LVHR, Bencini et al [21] examined 146 cases in which defect area was reported to have no relationship with hernia recurrence, whereas a study of 71 cases found a significant increase in recurrence with those requiring larger mesh attributing it to a larger defect size [22]. A recent study by Helgstrand et al [36], analyzing 3258 incisional hernia repairs from the Danish Ventral Hernia Database found that hernia defect diameter >7 cm was associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In smaller series of LVHR, Bencini et al [21] examined 146 cases in which defect area was reported to have no relationship with hernia recurrence, whereas a study of 71 cases found a significant increase in recurrence with those requiring larger mesh attributing it to a larger defect size [22]. A recent study by Helgstrand et al [36], analyzing 3258 incisional hernia repairs from the Danish Ventral Hernia Database found that hernia defect diameter >7 cm was associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Although recurrence continues to be an important hernia outcomes benchmark, patient QOL has become an increasingly important measure of surgical excellence [10e12]. Although a number of factors have been shown to influence QOL outcomes following VHR [10,17e19] and defect size has been shown to have a relationship with ventral hernia recurrence [22,24], our goal was to evaluate the direct correlation of defect width, length, and overall size on postoperative QOL. In this study, using an international database of patient-reported QOL outcomes, we have shown that large hernia defect width, length, and area all share a direct relationship with acute and chronic postoperative discomfort following VHR.…”
Section: Discussionmentioning
confidence: 99%
“…. A total of 51 reports with 6950 participants were included. Two reports had overlapping participants with an earlier study, so there were 49 studies with a unique population.…”
Section: Resultsmentioning
confidence: 99%
“…The surface under the cumulative ranking curve (SUCRA) simplifies the ranking of a treatment's probability of being better than another treatment, although it 35 150 (P) 40 13 Permanent and absorbable tacks with sutures Ferrari et al 36 69 (R) 41 73 Permanent tacks Ferrari et al 37 100 (I) 24 79⋅2 Permanent tacks Frantzides et al 38 208 (I) 24 173 Permanent staples Lahon et al 39 74 (I) 13 n.r. Permanent tacks Novitsky et al 40 163 ( 45 64 (66 P) 10 117⋅9 Permanent tacks with sutures Bucher et al 46 52 ( Values in parentheses are proportions unless indicated otherwise; *values are median (range) of mean and median values extracted from the individual studies.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…5,6,9,10,21,22 There is no doubt that some of the patients disconcertingly developed pain suggestive of peritonitis presumably as a reaction to the mesh in the first day or second day postoperatively. These dimensions are slightly smaller than those reported by other studies with a median mesh area of 322.5 cm 2 .…”
Section: Discussionmentioning
confidence: 99%